1984
DOI: 10.1042/cs0660269
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Reduced Sodium Intake on Post-Renal Transplantation Hypertension in Rats

Abstract: 1. In an experimental model of post-renal transplantation hypertension in rats, we studied the effect of a reduction of sodium intake on the development of this type of hypertension. 2. Systolic blood pressure, plasma- renin concentration and renal function were measured regularly in recipients of an allogeneic kidney transplant that had previously undergone active immunological enhancement. 3. Transplant recipients on a normal diet showed a rise in systolic blood pressure during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Either sodium restriction or the prevention of chronic rejection, i.e., a more successful immunosuppression, should prevent the development of hypertension. As shown in the present and a previous study [3] we found both to be effective.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Either sodium restriction or the prevention of chronic rejection, i.e., a more successful immunosuppression, should prevent the development of hypertension. As shown in the present and a previous study [3] we found both to be effective.…”
Section: Discussionsupporting
confidence: 73%
“…From the present and previously published results [2,3,11] we postulate that in our rat model of postrenal trans plantation hypertension the increase in SBP is the result of the following chain of events. Pretreatment with donor strain blood partially suppresses the rejection process, leading to a chronic type of rejection.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Non-immunologic factors are increasingly regarded as important for the prognosis of the transplant. In humans, investigations of changes on the tubular level are hardly possible, and only a few functional studies in animals are available (12)(13)(14)(15)(16)(17)(18)(19)(20). No direct data exist on expression and function of transporters and receptors involved in transport after renal transplantation.…”
mentioning
confidence: 99%